Modifying equipment in early skill development: A Tennis Perspective - Buszard, T.; Farrow, D.; Reid, M.; Masters, R. S. W. (Research Quarterly for Exercise and Sport, 2014)
Purpose: The International Tennis Federation recently launched a worldwide campaign advocating the use of equipment scaling for children learning to play tennis. The aim of this study was to investigate the influence that varying racquet sizes and ball compressions had on children's ability to play a forehand groundstroke. Method: This was a quantitative repeated-measures design experiment. Children were required to perform a forehand hitting task using each of 9 combinations of tennis racquets and balls (i.e., 3 racquet sizes × 3 ball compressions). Children's hitting performance was measured using a points system. The aim for the children was to score as many points as possible. Hitting technique was measured via video replay. Results: Hitting performance was best when the smallest racquet combined with the ball with the least compression was used. The ball with the least compression also promoted 2 technique benefits: swinging the racquet from low to high and striking the ball in front and to the side of the body. Conclusions: This study demonstrated the benefits for young children playing with scaled racquets and low-compression balls. The findings are discussed with regards to their relevance to theories of skill acquisition.